Inguinal bladder hernia associated with vesico-ureteric reflux. Issue 798 (April 1992) - Noble, J. G.; Christmas, T. J.; Chapple, C. R.; Rickards, D.
Abstract : The urinary bladder is frequently found as a component of inguinal herniae. This report describes a case of 'bladder hernia' associated with vesico-ureteric reflux. The current methods of investigation and subsequent treatment for this condition are reviewed along with the possible underlying cause of vesico-ureteric reflux in this case.